2018
DOI: 10.1007/s40735-018-0165-9
|View full text |Cite
|
Sign up to set email alerts
|

Some Thoughts on Mapping Tribological Issues of Wind Turbine Blades Due to Effects of Onshore and Offshore Raindrop Erosion

Abstract: This paper represents the investigation of liquid impacts on wind turbine blade materials in the simulation of onshore and offshore environmental conditions. G 10 epoxy glass laminate was used as a specimen material. The experimental work was carried out on a raindrop erosion test rig at the varying angles of attack for a range tip speed. Two solutions, i.e. pure and salt water, were used to highlight the effects of offshore environment on this material when it is being used as wind turbine blades. Test result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Previous work on this topic by the current research group showed similar results to the saltwater exposure in this investigation. This had concluded that the saltwater proved more erosive when subject to high velocity impacts from the leading edge of the turbine blade and would create larger, more destructive cracks and loss of material from the sample [15]. The added effect of the more consistent wind from offshore conditions with the sea water climate is conducive to an erosive atmosphere and hence a short life span of turbine blades.…”
Section: Rainfall Mapmentioning
confidence: 99%
“…Previous work on this topic by the current research group showed similar results to the saltwater exposure in this investigation. This had concluded that the saltwater proved more erosive when subject to high velocity impacts from the leading edge of the turbine blade and would create larger, more destructive cracks and loss of material from the sample [15]. The added effect of the more consistent wind from offshore conditions with the sea water climate is conducive to an erosive atmosphere and hence a short life span of turbine blades.…”
Section: Rainfall Mapmentioning
confidence: 99%
“…At the circumference of the swing arm includes needles which provide The experimental rig used for this investigation was an existing setup within the tribology department at The University of Strathclyde. This rig was previously used to collect experimental data for the paper titled "Some Thoughts on Mapping Tribological Issues of Wind Turbine Blades Due to Effects of Onshore and Offshore Raindrop Erosion" [13]. Adjustments were made to this rig to allow a bending stress to be applied to the sample.…”
Section: Methodology and Test Apparatusmentioning
confidence: 99%
“…To make this data from the experiments more relatable with the literature, the impact angle was changed from the angle of the sample holder which was used in the previous wear maps to the angle the droplet makes on the sample. In comparison to the previous salt water experiments [13], during the removal of the samples from the rig, the samples were given a short wash in order to minimise the quantity of salt crystals on and within the sample.…”
Section: Post Processingmentioning
confidence: 99%
“…A wastage map was created using the mass losses recorded during testing with respect to varying rain droplet diameter and linear velocity. Previous research on wastage maps for whirling arm rain erosion rigs from the group have addressed this issue, [20][21][22][23][24]. Initial parameters for low, medium and high mass loss had to be chosen.…”
Section: Raindrop Erosion Mapsmentioning
confidence: 99%